(untitled) (Scientific journal of the Fergana State University, 2023)
This article provides information on the functionality of the polysindeton phenomenon, which is one of the syntactic figures studied in the context of poetic syntax. Also, the characteristics of polysindeton as a multifunctional syntactic figure are described on the materials of the Uzbek language